Lumen Loss at 1 Year After Bare Nitinol Stent Implantation in the Superficial Femoral Artery. (February 2021) - Ito, Nobuhiro; Takahara, Mitsuyoshi; Soga, Yoshimitsu; Hiramori, Seiichi; Hirose, Kaoru; Tomoi, Yusuke; Ando, Kenji
Purpose: To investigate lumen loss (LL) at 1 year after bare nitinol stent (BNS) implantation for de novo superficial femoral artery (SFA) lesions. Materials and Methods: The subjects were 701 consecutive patients (mean age 74±9 years; 492 men) with 817 de novo SFA lesions treated with BNS implantation between January 2004 and September 2015. The mean lesion length was 141±88 mm and the mean vessel diameter was 5.4±0.9 mm. The endpoint was LL at 1 year after BNS implantation. Secondary outcomes were restenosis and target lesion revascularization (TLR) estimated using the Kaplan-Meier method; estimates are reported with the 95% confidence interval (CI). LL was defined as the minimum lumen diameter immediately after BNS implantation minus that at 1 year measured by angiographic quantitative vessel analysis. The distribution of LL in the overall population was estimated using an accelerated failure time model. Results: Mean LL at 1 year was estimated to be 1.74±1.28 mm (95% CI 1.63 to 1.84). Current smoking was positively associated with LL (p=0.015), whereas lack of cilostazol use was correlated with an increase in LL (p=0.001). Reference vessel diameter and lesion length did not have any significant association with LL at 1 year. The 1-year cumulative estimate of restenosis was 25% (95% CI 22% to 28%); the corresponding value for TLR was 18% (95% CI 15% to 21%). Conclusion: Mean LL progressed by at least 1.6 mm up to 1 year after BNS implantation. The risk factors for increased LL were current smoker and lack of cilostazol use.